Case Report on Esophageal Coin Management at District Hospital - Gupta, S; Sharma, N; Thakali, K (Journal of Gandaki Medical College-Nepal, 2018)
Accidental foreign body ingestion is commonly encountered in the pediatric population, with a peak incidence between the ages of six months and three years. Since the act may go unnoticed, the child may present late. Here, we report a case of an 11 year old boy who present at Lamjung District Hospital after 24 hours of ingestions of two rupee Indian coin. To the best of our knowledge this is the first time we describe a case report on coin removal at district hospital of Nepal. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 58-60